(untitled) (Jurnal AbdiMas Nusa Mandiri, 2025)
The interest of the Indonesian people in continuing their education to higher education levels is still relatively low, at only 6.68% of the total population of Indonesia (18.7/280 million people). Lampung is one of the provinces facing this issue, with data from 2023 showing that 77.36% of high school graduates in Lampung Province do not continue their education to higher education levels. Ringin Jaya Village is one of many villages in Lampung Province where students have a low interest in continuing their education to higher education levels. The main factors causing this are the limited number of schools, the family’s economic conditions, and the lack of understanding regarding the importance of higher education. However, the 1945 Constitution of the Republic of Indonesia Article 31 Paragraph 1 mandates that "every citizen has the right to education." Therefore, based on these issues and mandates, the implementation of community service in the form of socializing the importance of continuing higher education is a service program that needs to be carried out. This socialization aims to provide students with an understanding of the importance of continuing higher education, including the various benefits they will gain by pursuing higher education. In addition, this socialization also provides information about scholarship opportunities that can help them reduce the costs of higher education. Through this service, it is hoped that students can be motivated to continue their education to higher education levels. The results of the community service show an increase in students’ knowledge about the benefits and importance of continuing higher education. This increase in knowledge helps them to enhance their motivation to continue their education up to the higher education level. The interest of the Indonesian people in continuing their education to higher education levels is still relatively low, at only 6.68% of the total population of Indonesia (18.7/280 million people). Lampung is one of the provinces facing this issue, with data from 2023 showing that 77.36% of high school graduates in Lampung Province do not continue their education to higher education levels. Ringin Jaya Village is one of many villages in Lampung Province where students have a low interest in continuing their education to higher education levels. The main factors causing this are the limited number of schools, the family’s economic conditions, and the lack of understanding regarding the importance of higher education. However, the 1945 Constitution of the Republic of Indonesia Article 31 Paragraph 1 mandates that "every citizen has the right to education." Therefore, based on these issues and mandates, the implementation of community service in the form of socializing the importance of continuing higher education is a service program that needs to be carried out. This socialization aims to provide students with an understanding of the importance of continuing higher education, including the various benefits they will gain by pursuing higher education. In addition, this socialization also provides information about scholarship opportunities that can help them reduce the costs of higher education. Through this service, it is hoped that students can be motivated to continue their education to higher education levels. The results of the community service show an increase in students’ knowledge about the benefits and importance of continuing higher education. This increase in knowledge helps them to enhance their motivation to continue their education up to the higher education level.